Advancements in Restorative Dentistry: A Systematic Review of Techniques and Materials - Aldhalai , Metaib; Almansour , Hamad Hatim; Alyami, Saleh Ali Hassan; alsagri, Mohammed mana Mohammed; Al-Thibah, Ibrahim Ali Ali; Alnasaib, Yahya Jaber; AlYami, Mansour Mahdi Abdullah (Journal of Ecohumanism, 2024)
The field of restorative dentistry has experienced significant advancements, driven by the demand for aesthetic, durable, and minimally invasive treatment options. This systematic review evaluates recent developments in restorative techniques and materials, focusing on their clinical effectiveness, patient-centered outcomes, and limitations. Key advancements include minimally invasive techniques such as air abrasion and the Hall Technique, which aim to preserve natural tooth structure and reduce patient discomfort. Additionally, digital innovations like CAD/CAM and 3D printing have improved the precision and efficiency of dental restorations, allowing for same-day, custom-fit prosthetics that enhance patient satisfaction. The introduction of advanced materials—including nano-filled composites, biocompatible ceramics, and fluoride-releasing glass ionomers—has further improved the durability and aesthetic quality of restorations. Despite these benefits, challenges remain, including the high cost of adopting new technologies, the need for specialized training, and the limited availability of long-term data on some materials. This review concludes by highlighting future directions, such as the potential of biomimetic and regenerative materials, as well as artificial intelligence in treatment planning. These advancements collectively point towards a more effective and patient-focused future for restorative dentistry.